Complex Treatment for Sterile Pancreonecrosis - Yu. V. Nikiforov; S. V. Mikhailusov; Ye. V., Moiseyenkova; A. Yu. Yudin; A. V. Vorykhanov; A. V. Chirkov (Общая реаниматология)
The clinical course of sterile pancreonecrosis (SPN) (1992 Atlanta classification of acute pancreatitis) and intensive care measures were retrospectively analyzed in 496 patients with this condition. The diagnosis of SPN was established by a complex of clinical, biochemical, and instrumental studies (abdominal ultrasonography, gastroduodenoscopy, if needed, diagnostic laparoscopy). On admission, 5.6% of the patients underwent endoscopic papillosphincterotomy, 49.0% had Wirsung’s duct decompression via pancreatic juice aspiration. Endoscopic nasointensinal intubation was conducted in 75.8% of cases. When enzymatic peritonitis developed, laparoscopic abdominal drainage was carried out with 5 drains for _ peritoneal lavage (65.5%). The efficiency of medical measures was evaluated from the course and outcome of the disease. The authors analyzed 14-day mortality, the clinical and morphological regression of pancreonecrosis, the incidenceof local complications (acute fluid accumulations (AFA), and the incidence of infected pancreonecrosis (IPN). Results. According to the severity of the underlying condition, the patients were divided into two groups. Group 1 (SAPS < 9; mean score 7.4±0.8) included 338 (68.4%) of the 496 patients; Group 2 (SAPS > 9; mean score 12.5±1.8) comprised 158 (31.6%) patients. The baseline condition of patients was determined by the involvement extent of the pancreas and retroperitoneal fat. In Groups 1 and 2, mortality was 7.1 and 19.0%, respectively (p=0.000). Overall mortality was 10.9%. Cessation and regression of tissue necrotic changes in the pancreas and retroperitoneal fat were observed in 49.7% of cases in Group 1 and only in 12.7% in Group 2 (p=0.000). AFA was diagnosed in 43.2% of patients in Group 1 and in 68.4% in Group 2 (p=0.000). Adequate intestinal stimulation, nutritional support, and antibacterial therapy caused a mortality reduction in SPN irrespective of the SAPS severity. The abortive course of SPN was more frequently recorded in both groups when balanced multicomponent infusion therapy was performed in the first 24 hours of the disease. Regression of necrosis was also seen in the use of clinically effective gastrointestinal tract (GIT) stimulation, medical sedation, blockade of the secretory function of the gland, and antibacterial therapy in Group 1, and during adequate prolonged epidural anesthesia in Group 2. AFA was less frequently observed in the use of somatostatin analogues in Group 1 and complex infusion therapy and during adequate nutritional support only in Group 2. Fewer cases of infection in SPN were noted after effective GIT stimulation and antibiotic therapy in both groups, but during balanced (tube, parenteral) feeding in Group 1. Thus, adequate combined medical intensive therapy in Group 1 considerably improves the clinical course and outcomes of the disease. The results of intensive care were worse in extensive involvement of the pancreas and retroperitoneal fat (SAPS > 9). Key words: pancreonecrosis, intensive care.